Cathepsins in Bacteria-Macrophage Interaction: Defenders or Victims of Circumstance? - Szulc-Dąbrowska, Lidia; Bossowska-Nowicka, Magdalena; Struzik, Justyna; Toka, Felix N. (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages are the first encounters of invading bacteria and are responsible for engulfing and digesting pathogens through phagocytosis leading to initiation of the innate inflammatory response. Intracellular digestion occurs through a close relationship between phagocytic/endocytic and lysosomal pathways, in which proteolytic enzymes, such as cathepsins, are involved. The presence of cathepsins in the endo-lysosomal compartment permits direct interaction with and killing of bacteria, and may contribute to processing of bacterial antigens for presentation, an event necessary for the induction of antibacterial adaptive immune response. Therefore, it is not surprising that bacteria can control the expression and proteolytic activity of cathepsins, including their inhibitors – cystatins, to favor their own intracellular survival in macrophages. In this review, we summarize recent developments in defining the role of cathepsins in bacteria-macrophage interaction and describe important strategies engaged by bacteria to manipulate cathepsin expression and activity in macrophages. Particularly, we focus on specific bacterial species due to their clinical relevance to humans and animal health, i.e., Mycobacterium, Mycoplasma, Staphylococcus, Streptococcus, Salmonella, Shigella, Francisella, Chlamydia, Listeria, Brucella, Helicobacter, Neisseria, and other genera.